The effect of subclinical experimental Cowdria ruminantium infection in ewes on the growth and milk consumption of pre-weaning lambs - Martínez, T.A.; Meltzer, M.I.; Perry, Brian D.; Burridge, M.J.; Mahan, S.M. (Elsevier, 1999)
An alternative control option for heartwater (Cowdria ruminatium infection) is the establishment and maintenance of endemic stability which would lessen the existing dependence on acaricides. In an endemically stable state, animals become infected by vaccination or natural challenge at an early age, following which the immunity so created is boosted by continuing tick challenge. In this study, growth rates, health and hematological parameters were monitored at regular intervals for lambs born to two matched groups of ewes until weaning at 4 mo of age. One group of ewes was infected multiple times with Cowdria ruminantium; the other group remained uninfected. The overall mean leucocyte count of lambs born to infected ewes was significantly lower than that of lambs born to uninfected ewes (P=0.04). However, there were few other significant differences in the other hematological data between the two groups. The mean birth weight of single lambs born to unifected ewes (4.6 kg) was significantly higher than the mean birth weight of single lambs born to infected ewes (4.4 kg) (P=0.02). Trends in milk consumption and growth rates were similar for the two groups, with few significant differences detected. Likewise, there were no significant differences in the incidences of health problems or pre-weaning mortalities between the two groups of lambs. The results of this study indicate that there is no detectable effect on productivity of pre-weaning lambs when their dams are carriers of C. ruminantium - a situation likely to occur in an endemically stable state. Hence, maintenance of endemic stability would be a suitable control option for heartwater.